Thrombin generation assays are superior to traditional tests in assessing anticoagulation reversal in vitro - Gatt, Alex; van Veen, Joost J; Woolley, Anita M; Kitchen, Steve; Cooper, Peter; Makris, Michael (Thrombosis and haemostasis, 2008)
Even though new anticoagulants are being devised with the notion that they do not require regular monitoring, when bleeding occurs, it is important to have an antidote and a reliable test to confirm whether the anticoagulant effects are persisting. We examined the effects of five heparinoids, unfractionated heparin (UFH), tinzaparin, enoxaparin, danaparoid and fondaparinux on the traditional APTT and anti-Xa assays as well as on the calibrated automated thrombogram (CAT). We also studied the ability of protamine sulphate (PS), NovoSeven, FEIBA and FFP to reverse maximum anticoagulation induced by the different heparinoids. The CAT was the only test to detect the coagulopathy of all the anticoagulants. PS produced complete reversal of UFH, and this could be monitored with all three tests. Tinzaparin can also be completely neutralised in vitro with high doses of PS, but the maximum enoxaparin reversal achieved with PS is only approximately 60%. Fondaparinux does not significantly affect the APTT and PS has no significant effect on its reversal. Only NovoSeven was able to correct the fondaparinux induced CAT abnormalities whilst having no effect on the anti-Xa level. None of the reversal agents was very effective in danaparoid spiked plasma but NovoSeven, at high dose, increased the ETP by 40% and reduced the anti-Xa level from 0.93 to 0.78 IU/ml. We conclude that the CAT is superior to the traditional coagulation tests in that it not only detects the coagulopathy of all the heparinoids but can be also be used to monitor their reversal.